A mixed approach for urban flood prediction using Machine Learning and GIS - Motta, Marcel (2021)
Motta, M., de Castro Neto, M., & Sarmento, P. (2021). A mixed approach for urban flood prediction using Machine Learning and GIS. International Journal of Disaster Risk Reduction, 56, 1-13. [102154]. https://doi.org/10.1016/j.ijdrr.2021.102154